An energy-friendly alternative in the large-scale production of soybean oil. (15th January 2019) - Kong, Weibin; Baeyens, Jan; De Winter, Kjerstin; Urrutia, Andrés Reyes; Degrève, Jan; Zhang, Huili
Abstract: Soybean oil is widely used as cooking oil, whereas the soybean cake is a valuable ingredient for animal food. The extraction of soybean oil is an energy-intensive process, with additional significant impact on the environment via the wastewater and hexane emissions. The research investigated different ways to minimize the energy consumption. In a traditional process, both direct (live) steam and indirect steam heating (jackets, tubular exchangers) are used to deliver the required heat duty. Direct steam injection is restricted to the first evaporator and the stripper, for a total of 620 kg/h. Indirect steam is also applied in the evaporators for a total of 6.44 MW. The desolventizing process requires a steam energy input of 8.15 MW. Integration of a heat exchanger network in the evaporation and stripping part of the process reduces the amount of direct steam usage from 620 kg/h to 270 kg/h and of the indirect heat duty from 6.44 to 5.05 MW. In the cake desolventizing part of the process, the energy requirement is reduced from 8.15 to 2.12 MW. The overall gross energy saving is hence ∼50%. The improvements moreover reduce both the waste water loadings by 56.5% and the CO2 emissions by 62.5%. Hexane emissions are moreover significantly (>90%) reduced. Graphical abstract: Detailed flow sheet of the entire production process of Soybean oil . 1. Leaching; 2. Fluidized bed desolventizer/toaster/cooler; 3. EVAP1; 4. EVAP2; 5. STRIP; 6. Condenser; 7. Filter; 8. Cascade gas membrane separator; 9. Cascade gas membrane separator; 10. Vacuum pump; 11. water/hexane separator; 12. Waste water treatment. Highlights: The extraction of vegetable oils is an energy-intensive process. Process improvements for the production of soybean oil were investigated. Energy savings by the individual and combined improvements are calculated, and result in a ∼50% reduction in steam consumption. Environmental benefits involve waste water reduction and a reduction of the CO2 footprint.